The mediating role of coping styles in the relationship between personality traits and occupational well-being among nursing staff - Wang, Fei; Li, Sheng; Liu, Wenjie; Li, Yifei; Jia, Qing; Wang, Jinyu (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to quantify the mediating effects of positive and negative coping styles on the relationship between the Big Five personality traits and occupational well-being among nurses. The findings aim to provide a scientific basis for optimizing psychological health interventions for nurses.MethodsA cross-sectional study was conducted, involving 9,578 nursing staff from over 50 hospitals of varying tiers in Lanzhou, China. Standardized scales—the Chinese Big Five Personality Inventory-Brief (CBF-PI-B), Simplified Coping Style Questionnaire (SCSQ), and Occupational Well-being Scale for Healthcare Workers—were administered. Mediation effects were tested using the Bootstrap method, with adjustments for covariates including gender, age, and department.ResultsPersonality traits showed significant correlations with occupational well-being: Extraversion, conscientiousness, agreeableness, and openness were positively correlated with well-being (r = 0.337 to 0.400), while neuroticism was negatively correlated (r = −0.338). Coping styles played a pivotal mediating role: Neuroticism indirectly reduced well-being through negative coping strategies (e.g., problem avoidance), while conscientiousness, agreeableness, openness, and extraversion correlated with positive coping strategies (e.g., active problem-solving) and higher well-being. The mediating effect of positive coping was substantially larger, accounting for 23.69 to 31.93% of the total effects, whereas negative coping accounted for less than 5.69%.ConclusionPersonality traits indirectly affect occupational well-being via positive or negative coping strategies, with proactive coping serving as the critical pathway for well-being enhancement. This study reveals an asymmetry in the mediating mechanism, where the efficacy of positive coping far outweighs that of negative coping. These insights offer novel perspectives for developing targeted interventions, such as personality assessment-guided coping skills training. These findings support a ‘Coping Efficacy Asymmetry Model’ providing a new framework for interventions that prioritize building positive coping skills to enhance nurse well-being and support healthcare system resilience.